2009
DOI: 10.1038/mp.2009.94
|View full text |Cite
|
Sign up to set email alerts
|

Sex, trauma, stress hormones and depression

Abstract: Although few studies dispute that there are gender differences in depression, the etiology is still unknown. In this review, we cover a number of proposed factors and the evidences for and against these factors that may account for gender differences in depression. These include the possible role of estrogens at puberty, differences in exposure to childhood trauma, differences in stress perception between men and women and the biological differences in stress response. None of these factors seem to explain gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
4
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(154 citation statements)
references
References 53 publications
4
143
4
3
Order By: Relevance
“…Only male subjects were used to reduce the known confound of sex-steroids on GR activation (Young and Korszun, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Only male subjects were used to reduce the known confound of sex-steroids on GR activation (Young and Korszun, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These gender differences could be explained by several factors. The sensitivity to PS differs between men and women (Young and Korszun, 2010). Overall, men are more physically active (Zitouni and Guinhouya, 2012;Peer et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Childhood sexual abuse has also been strongly linked to psychiatric risk (Felitti et al 1998;Kendler et al 2002;Nelson et al 2002;Kendler et al 2004;Kendler et al 2006;Fergusson et al 2008). Though the mechanisms involved are not yet entirely clear, there is mounting evidence that these associations between adverse childhood experiences and psychiatric risk are mediated by permanent effects of repeated stressors on HPA axis reactivity (Heim et al 2008;Pariante and Lightman 2008;Lupien et al 2009;Romeo 2010;Young and Korszun 2010). Several studies have shown elevated rates of childhood sexual abuse and risky family environment in nonheterosexuals (Cameron and Cameron 1995;Lenderking et al 1997;Fergusson et al 1999;Paul et al 2001;Tomeo et al 2001;Balsam et al 2005;Arreola et al 2008;Alanko et al 2009;Zietsch et al in press).…”
Section: Adverse Childhood Experiences -Risky Family Environment and mentioning
confidence: 99%